Dim Light at Night and Constant Darkness: Two Frequently Used Lighting Conditions That Jeopardize the Health and Well-being of Laboratory Rodents - González, Mónica M. C. (Frontiers in Neurology, 2018)
In mammals, physiological and behavioral circadian rhythms are regulated by the suprachiasmatic nucleus (SCN) of the hypothalamus. This central control allows organisms to predict and anticipate environmental change, as well as to coordinate different rhythmic modalities within an individual. In adult mammals, direct retinal projections to the SCN are responsible for resetting and synchronizing physiological and behavioral rhythms to the light-dark (LD) cycle. The objective of this review is to increase awareness, within the scientific community and commercial providers, of the fact that laboratory animals can experience a number of adverse health and welfare outcomes attributed to commonly-used lighting conditions in animal facilities during routine husbandry and scientific procedures. There is increasing evidence that exposure to dim light at night, as well as chronic constant darkness, can challenge the circadian system of laboratory rodents, resulting in disrupted circadian rhythms, neural death, a depressive-behavioral phenotype, and the deregulation of metabolic, physiological and synaptic plasticity in both the short and long terms. The normal development and good health of laboratory animals requires cyclical light entrainment, adapted to the solar cycle of day and night, with null light at night and safe illuminating qualities during the day. We therefore recommend increased awareness of the limited information available with regards to lighting conditions, and therefore that lighting protocols must be taken into consideration when designing experiments and duly highlighted in scientific papers. This practice will help to ensure the welfare of laboratory animals and increase the likelihood of producing reliable and reproducible results.